Simultaneous distribution of the fractional parts of Riemann zeta zeros. Issue 1 (29th December 2016) - Ford, Kevin; Meng, Xianchang; Zaharescu, Alexandru
Abstract: In this paper, we investigate the simultaneous distribution of the fractional parts of α 1 γ, α 2 γ, ..., α n γ , where n ⩾ 2, α 1, α 2, ..., and α n are fixed distinct positive real numbers, and γ runs over the imaginary parts of the non‐trivial zeros of the Riemann zeta‐function.